Multiparametric characterization of red blood cell physiology after hypotonic dialysis based drug encapsulation process - Mélanie Robert; Bastien Laperrousaz; Diana Piedrahita; Emilie-Fleur Gautier; Travis Nemkov; Florian Dupuy; Elie Nader; Virginie Salnot; Patrick Mayeux; Angelo D'Alessandro; Catherine Lavazec; Philippe Joly; et al. (Elsevier, 2022)
Red blood cells (RBCs) can act as carriers for therapeutic agents and can substantially improve the safety, pharmacokinetics, and pharmacodynamics of many drugs. Maintaining RBCs integrity and lifespan is important for the efficacy of RBCs as drug carrier. We investigated the impact of drug encapsulation by hypotonic dialysis on RBCs physiology and integrity. Several parameters were compared between processed RBCs loaded with l-asparaginase ("eryaspase"), processed RBCs without drug and non-processed RBCs. Processed RBCs were less hydrated and displayed a reduction of intracellular content. We observed a change in the metabolomic but not in the proteomic profile of processed RBCs. Encapsulation process caused moderate morphological changes and was accompanied by an increase of RBCs-derived Extracellular Vesicles release. Despite a decrease in deformability, processed RBCs were not mechanically retained in a spleen-mimicking device and had increased surface-to-volume ratio and osmotic resistance. Processed RBCs half-life was not significantly affected in a mouse model and our previous phase 1 clinical study showed that encapsulation of asparaginase in RBCs prolonged its in vivo half-life compared to free forms. Our study demonstrated that encapsulation by hypotonic dialysis may affect certain characteristics of RBCs but does not significantly affect the in vivo longevity of RBCs or their drug carrier function.